Surface intermediate species of the 4-isobutylacetophenone adsorption-reaction over fosfotungstic Wells-Dawson heteropoly acid - Matkovic, Silvana R. (2009)
Surface adsorbed species of isobutybenzene and 4-isobutylacetophenone on bulk fosfotungstic Wells-Dawson acid H6P2W18O62.xH2O (HPA) have been screened in the present investigation. The evolution of chemisorbed species towards products was followed through infrared spectroscopy of systems containing liquid reactants and the solid acid kept at various temperatures. 4-Isobutylacetophenone adsorbs on Brønsted acid sites of the heteropoly acid and further reacts towards a condensation product similarly to the reaction of acetophenone over other acid materials such as, mordenite, niobic acid and sulfated zirconia. The condensation product possesses well defined infrared signals at 1654 cm-1 and 1597 cm-1 that resemble the carbonyl stretching vibration and the double bond of dypnone C6H5COHC=C(CH3)C6H5. Additional signals at 1221 cm-1 and a shoulder at 1284 cm-1 ascribed to the vibration of the C6H5 species in the C6H5COHC= group, give more evidences of the formation of a chalcone type compound. A reaction mechanism of the Aldol condensation of 4-isobutylacetophenone through an enol reactive intermediate is proposed.